Labor law in Colombia and application of international regulations - Angulo Marquinez, Diana Maryury (DIXI, 2023)
Subject and scope: The purpose of this research work is to analyze the importance of labor law as applied in Colombia, and how it has had an international impact. It examines both its origin and its link with the Colombian legal system, taking into account the change brought about by the 1991 Constitution in this area.Characteristics: The paper begins by exploring the background of research on labor issues in Colombia and then delves into the issue of reinforced labor stability from a comparative perspective. It highlights the need for Colombia to further incorporate international treaties on labor matters, without resorting to tutela as a protection mechanism.Findings: Based on the review of the literature, it is evident that Colombia has a long way to go in terms of the incorporation of international treaties in labor matters. However, the importance of not resorting to tutela as the only form of protection is emphasized.Conclusions: Colombia is a social state of law in constant growth, and in this process it is important to take into account the protection of the labor rights of women, who are subjects of protection and must enjoy their rights.
Keywords: conventionality control; reinforced labor stability; social rule of law; labor law; international norms; constitutional block